Managing varicella zoster virus contact and infection in patients on anti-rheumatic therapy. (29th May 2017) - Cates, Matthew; Donati, Matthew; Gillet, Sophie; Ustianowski, Andrew; Galloway, James
Abstract: Chickenpox and shingles can be more severe and occasionally life threatening in immunosuppressed patients. As such, some groups warrant a more detailed history, serological testing and consideration of prophylaxis following contact with the virus. Active disease may also require more aggressive treatment with antivirals. Guidance for the use of varicella zoster immunoglobulin has recently been updated by Public Health England with important implications for rheumatology patients.